2001
DOI: 10.1146/annurev.med.52.1.503
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Antipsychotics: New Directions and New Challenges in the Treatment of Schizophrenia

Abstract: "Atypical" antipsychotics represent a new generation of antipsychotics with a significantly lower incidence of extrapyramidal side effects (EPS), as well as little or no effect on prolactin elevation. These advantages constitute a major improvement in the treatment of patients with schizophrenia. The exact mechanisms that make these drugs atypical is not clear. However, a preferential action on serotonin 5-HT2 or D4 receptors, or a more rapid dissociation from the dopamine D2 receptor, may account for atypical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
187
0
7

Year Published

2002
2002
2010
2010

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 287 publications
(198 citation statements)
references
References 72 publications
4
187
0
7
Order By: Relevance
“…Second, because our experiments designed to identify the behavioral mechanisms of antipsychotics were carried out primarily by using haloperidol, whether the same mechanisms are also responsible for the effects of atypical antipsychotics such as clozapine or quietapine has not been tested and is still an open question. Because of the unique receptor binding profile associated with each antipsychotic drug (Kapur and Remington, 2001), it is possible that some antipsychotics may work differently via different neurochemical mechanisms (eg 5-HT 2A , a 2 adrenoceptors). Finally, the subjects used in this study were normal rats, whereas antipsychotics are usually used to treat patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Second, because our experiments designed to identify the behavioral mechanisms of antipsychotics were carried out primarily by using haloperidol, whether the same mechanisms are also responsible for the effects of atypical antipsychotics such as clozapine or quietapine has not been tested and is still an open question. Because of the unique receptor binding profile associated with each antipsychotic drug (Kapur and Remington, 2001), it is possible that some antipsychotics may work differently via different neurochemical mechanisms (eg 5-HT 2A , a 2 adrenoceptors). Finally, the subjects used in this study were normal rats, whereas antipsychotics are usually used to treat patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Typical and atypical neuroleptics are known to bind with different affinities to dopamine and serotonin receptors (29), but the downstream effects of these drugs are not well known. When patients were subdivided according to medication received, we noticed that the expression of all OR genes tended to differ among the three subgroups (atypical neuroleptic, typical neuroleptic, and not treated with neuroleptics before death).…”
Section: Potential Involvement Of the Human Qki Gene In Schizophreniamentioning
confidence: 99%
“…Given its high affinity for atypical antipsychotic drugs that constitute a major improvement in the treatment of schizophrenia (Van Tol et al, 1991;Kapur and Remington, 2001), D 4 receptor has been suggested to play an important role in PFC cognitive functions and therefore to be involved in the pathophysiology of neuropsychiatric disorders (for review, see Oak et al, 2000). In agreement with this, D 4 receptor antagonists have been found to alleviate stress-induced working memory deficits in monkeys (Murphy et al, 1996) and to ameliorate the cognitive deficits exhibited by monkeys after long-term treatment with the psychotomimetic drug phencyclidine (Jentsch et al, 1997(Jentsch et al, , 1999.…”
Section: Abstract: Dopamine Receptors; Gaba a Receptor Channels; Promentioning
confidence: 99%